Assessment and comparison of condylar position based on joint space dimensions and gelb 4/7 grid using CBCT - Sairam Vankadara; Baandhavi Akula; Kolluri Nissi (Wolters Kluwer Medknow Publications, 2021)
Background: Temporomandibular joint (TMJ) is a unique joint. An optimal position of the mandibular condyle in the glenoid fossa is a fundamental question in dentistry, and there is no quantitative standard. Thus, the most common condylar position in the glenoid fossa can be determined by the dimension of the joint space and Gelb 4/7 grid using cone-beam computed tomography (CBCT). Aim: To analyze the position of the condyle and joint spaces in the normal temporomandibular joint and to compare the efficacy of the Gelb 4/7 grid over dimensions of joint spaces to assess optimum condylar position using CBCT. Materials and Methods: CBCT images of 40 patients (right and left) without a history of TMJ disorders were selected. Anterior (Ajs), superior (Sjs), and posterior joint spaces (Pjs) on sagittal slices, medial (Mjs), and lateral (Ljs) on coronal view were measured and Gelb 4/7 grid on sagittal slices used to assess the condylar position. Results: Significant difference between right and left sides in Ajs, Sjs, Mjs, and Ljs values. Significant differences were noticed in Mjs, Ajs values between males and females. Centric position is the most common position of the condyle, and 4/7 position is the most common according to Gelb 4/7 grid. Conclusion: Gelb 4/7 position was found to be the most common anatomical position of the condyle in healthy TMJs, and centric relation position was the most common based on joint space dimensions.